2011
DOI: 10.1097/mao.0b013e31821c6c7b
|View full text |Cite
|
Sign up to set email alerts
|

Perception Threshold for Tilt

Abstract: The aim of this study was to determine the thresholds for perception of tilt and translation using 3 motion/tilt profile paradigms. Healthy subjects were submitted to the following: 1) unilateral and bilateral eccentric rotations (centrifugation), 2) whole body translatory decelerations opposite to the movement direction while seated on a linear sled, and 3) discrete slow velocity platform tilts. Subjects were instructed to verbally indicate the perceived direction of tilt or translation. Fifteen healthy subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 39 publications
3
9
0
Order By: Relevance
“…Our vestibular thresholds as a function of frequency in the dark are very similar to those recently reported for roll tilt by Valko et al (2012), and also quite similar to those recently reported by other groups at 2 Hz (Crane 2012b) and for low-velocity tilts using a detection task (Janssen et al 2011). Another study (Lagace-Nadon et al 2009) reported that visual roll tilt thresholds decreased with increasing temporal frequency, consistent with our findings.…”
Section: Dynamics Of Vestibular and Visual Perceptual Thresholdssupporting
confidence: 82%
See 1 more Smart Citation
“…Our vestibular thresholds as a function of frequency in the dark are very similar to those recently reported for roll tilt by Valko et al (2012), and also quite similar to those recently reported by other groups at 2 Hz (Crane 2012b) and for low-velocity tilts using a detection task (Janssen et al 2011). Another study (Lagace-Nadon et al 2009) reported that visual roll tilt thresholds decreased with increasing temporal frequency, consistent with our findings.…”
Section: Dynamics Of Vestibular and Visual Perceptual Thresholdssupporting
confidence: 82%
“…Roll rotation thresholds ({) are collected with the subject supine, so that the SCC are the primary motion cue. Pseudostatic-tilt thresholds (dashed line) are collected using very slow constant velocity tilts which stimulate primarily the otolith organ and are consistent with "otolith" thresholds determined by others (Janssen et al 2011). At low frequencies, roll tilt thresholds are consistent with the pseudostatic-tilt threshold, suggesting the brain relies primarily on otolith organ cues.…”
Section: Dynamics Of Vestibular and Visual Perceptual Thresholdsmentioning
confidence: 59%
“…This finding indicates that tilt at the end of a roll adapter causes the RAE to persist. The 9° tilt at the end of the adapting stimulus, although small, is well above the tilt perception threshold (Janssen et al 2011), and prolonged the RAE perhaps by facilitating persistence of the effect of the adapting roll.…”
Section: Discussionmentioning
confidence: 99%
“…The threshold for perception of static tilt (postural vertical) has been previously measured as 4.4° (Mann and Dauterive 1949; Mann 1950) which is similar to the threshold measured using a centrifuge to change the vertical acceleration vector (Graybiel and Patterson 1955). A more recent study described the threshold of human tilt perception over a group of individuals as 1.9° – 5.6° (Janssen et al 2011). Thus in the current study the thresholds were almost certainly determined by the semicircular canal response to roll rather than by otolith and proprioceptive influences to tilt because at the threshold of roll perception the tilt (0.2°) was an order of magnitude smaller than the previously described thresholds of tilt perception (1.9 to 5.6°).…”
Section: Discussionmentioning
confidence: 99%
“…UCF was scored as median SVV angle and gain in each position and utricular percentage weakness. The normal range for static SVV is about 2° [13,16].…”
Section: Utricular Centrifugation (Ucf)mentioning
confidence: 99%